Amine-binding properties of salivary yellow-related proteins in phlebotomine sand flies - Sumova, Petra; Sima, Michal; Kalouskova, Barbora; Polanska, Nikola; Vanek, Ondrej; Oliveira, Fabiano; Valenzuela, Jesus G; Volf, Petr (Insect biochemistry and molecular biology, 2019)
The amine-binding properties of sand fly salivary yellow-related proteins (YRPs) were described only in Lutzomyia longipalpis sand flies. Here, we experimentally confirmed the kratagonist function of YRPs in the genus Phlebotomus. We utilized microscale thermophoresis technique to determine the amine-binding properties of YRPs in saliva of Phlebotomus perniciosus and P. orientalis, the Old-World vectors of visceral leishmaniases causative agents. Expressed and purified YRPs from three different sand fly species were tested for their interactions with various biogenic amines, including serotonin, histamine and catecholamines. Using the L. longipalpis YRP LJM11 as a control, we have demonstrated the comparability of the microscale thermophoresis method with conventional isothermal titration calorimetry described previously. By homology in silico modeling, we predicted the surface charge and both amino acids and hydrogen bonds of the amine-binding motifs to influence the binding affinities between closely related YRPs. All YRPs tested bound at least two biogenic amines, while the affinities differ both among and within species. Low affinity was observed for histamine. The salivary recombinant proteins rSP03B (P. perniciosus) and rPorASP4 (P. orientalis) showed high-affinity binding of serotonin, suggesting their capability to facilitate inhibition of the blood vessel contraction and platelet aggregation.
Keywords: Static Electricity; Salivary Proteins and Peptides; hmyzí proteiny; Phlebotomus; Protein Conformation; Salivary Glands; Phlebotomus orientalis; slinné proteiny a peptidy; Yellow-related protein; aminy; zvířata; Microscale thermophoresis; statická elektřina; Biogenic amine; Amines; Phlebotomus perniciosus; slinné žlázy; Salivary protein; Animals; Insect Proteins; konformace proteinů